SOCIO-ECOLOGICAL INNOVATION OF ROBUSTA COFFEE PROCESSING THROUGH CIRCULAR ECONOMY TECHNOLOGY TO IMPROVE THE WELFARE OF FARMER GROUPS - Welly, Yerisma; Sianipar, Martin Yehezkiel; Putra, Hendris Syah (LPPM Univ. Ibn Khaldun Bogor, 2025)
The application of circular economy technology in robusta coffee processing is a strategic approach to improve the sustainability and welfare of the farming community. This community service aims to develop socio-ecological innovations based on community mapping in supporting the implementation of circular economy technology. Through the Asset-Based Community Development (ABCD) approach, this service identifies relevant social structures, local assets, needs, and partnership networks to ensure the adoption of technologies appropriate to the local context. The results of the service show that the use of coffee waste as a new raw material, technology integration, and environmentally friendly processing processes can increase production efficiency while creating economic added value. In addition, community mapping plays an important role in strengthening farmer participation, building cross-sector collaboration, and creating inclusive innovation. This study recommends a community mapping-based approach as a foundation for a more sustainable and equitable transformation of coffee processing systems.